Alcances y límites de un proyecto ilustrado: la Sociedad de Amantes del País y el Mercurio Peruano - Guibovich Pérez, Pedro (2005)
The Society of Friends of the Country and its organ, Mercurio Peruano, were two of the most important manifestations of the illustrated culture of the Peruvian viceroyalty toward the end of the 18th century. There is an abundant bibliography on both topics which contends that both failed because of official censure which in turn was provoked by their critical discourse. This article questions that interpretation based on a study on the relationship between the Society and the Bourbon’s reformist policies and new  documentation.